When L1 takes precedence: revisiting semantic acquisition in diverse L2 learners - Han, Weifeng (Frontiers in Education, 2025)
This paper investigates the interaction between the Semantic Subset Principle (SSP) and first language (L1) influence in second language (L2) acquisition, focusing on ambiguous linguistic structures that involve subset-superset readings. Based on findings of a series of experimental surveys, this paper proposes that first language knowledge significantly impacts L2 semantic acquisition, often overriding the predictions of SSP. Learners tend to rely on the narrower interpretations present in their L1 when acquiring L2 structures, particularly in the absence of sufficient positive input for alternative readings in L2. The findings highlight challenges faced by culturally and linguistically diverse learners, including those with developmental language disorders, who may be particularly vulnerable to L1 interference. This paper proposes the updated First Language Interpretation Priority Principle (FLIPP), which posits that learners’ successful acquisition of subset-superset distinctions in an L2 is contingent upon these distinctions existing in their L1 and being reinforced by positive input from the L2. Implications for theory, practice, and policy-making are discussed, calling for inclusive and targeted pedagogical and clinical interventions to support diverse learners in multilingual settings.